Social Cohesion in Post-Genocide Rwanda : Local (Re)conceptions Beyond Global Definitions - Dahlmanns, Erika; Studies, Bayreuth Academy of Advanced African (University of Bayreuth African Studies Working Papers, 2025)
In light of global dynamics threatening the social ties that hold societies together, recent research has turned to exploring 'conceptions of social cohesion' in Africa. Focusing on Rwanda, this paper argues that while post-genocide government documents (1999-2012) align with globalized definitions of cohesion—emphasizing inclusive identity, trust, and cooperation—Rwanda's approach to rebuilding national unity is deeply rooted in localized notions. Rwandan notions of social cohesion revolve around 'culture' and 'kinship,' which throughout history have played a crucial role in (re)framing social orders in response to inter-group conflict and shifting conceptions of the nation. This case study suggests that beyond trust in institutions and fellow citizens, understanding the normative narratives and cultural frameworks that define social order, as well as the population's familiarity with these, is crucial to assessing cohesion—especially in contexts of nation-building where social trust has been eroded by violent conflict.
Keywords: Social cohesion; Rwanda; genocide; Reconciliation; identity politics; social identity; conflict transformation; conflict resolution; Culture; kinship; Tradition; Itorero; Intore; national unity; Nation Building; national identity; narratives; intermarriage